Prevalence, Attitudes, and Factors Motivating Conscientious Objection toward Reproductive Health among Medical Students - Darzé, Omar Ismail Santos Pereira; Barroso Júnior, Ubirajara (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective We have evaluated the prevalence of and the motivating factors behind the refusal to provide reproductive health services and the ethical knowledge of the subject among medical students from the Escola Bahiana de Medicina e Saúde Pública, in the state of Bahia, Brazil.Methods The present cross-sectional study involved 120 medical students. A questionnaire was utilized. The dependent variables were students' objections (or not) regarding three clinical reproductive health cases: abortion provided by law, contraceptive guidance to an adolescent without parental consent, and prescription of emergency contraception. The independent variables were age, gender, religion, ethical value, degree of religiosity, and attendance at worship services. Ethical knowledge comprised an obligation to state the reasons for the objection, report possible alternatives, and referral to another professional. Data were analyzed with χ2 tests and t-tests with a significance level of 5%.Results Abortion, contraception to adolescents, and emergency contraception were refused by 35.8%, 17.5%, and 5.8% of the students, respectively. High religiosity (p < 0.001) and higher attendance at worship services (p = 0.034) were predictors of refusing abortion. Refusal to provide contraception to adolescents was significantly higher among women than men (p = 0.037). Furthermore, 25% would not explain the reason for the refusal, 15% would not describe all the procedures used, and 25% would not refer the patient to another professional.Conclusion Abortion provided by law was the most objectionable situation. The motivating factors for this refusal were high commitment and religiosity. A reasonable portion of the students did not demonstrate ethical knowledge about the subject.
Keywords: legal abortion; adolescence; reproductive rights; medical education; women's health